2019
DOI: 10.1155/2019/3456719
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin Promotes the Osteogenesis of Human Mesenchymal Stem Cells via the ERK and Wnt/β-Catenin Signaling Pathways

Abstract: Dihydroartemisinin (DHA), which is considered to be one of the active compounds within Artemisia annua, has extensively been used in recent years as the most effective drug against malaria, having many biological functions including anticancer, antifungal, and immunomodulatory activities. However, DHA plays a role in the regulation of the proliferation and human mesenchymal stem cells (hMSCs) osteogenic differentiation that remains unknown. We explored DHA’s effect on hMSCs’ proliferation as well as the osteog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Extracellular signal-regulated kinase (ERK) pathway, also known as the Ras-Raf-MEK-ERK pathway, is involved in a variety of physiological processes such as cell proliferation, division, and survival [34,35]. Numerous studies have revealed that ERK signaling pathway plays vital roles in the osteogenic differentiation [36][37][38][39]. With regard to the relationship between HSPB7 and ERK signaling pathway, Naderi found HSPB7 overexpression in breast cancer cells reduced the level of p-ERK [18].…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular signal-regulated kinase (ERK) pathway, also known as the Ras-Raf-MEK-ERK pathway, is involved in a variety of physiological processes such as cell proliferation, division, and survival [34,35]. Numerous studies have revealed that ERK signaling pathway plays vital roles in the osteogenic differentiation [36][37][38][39]. With regard to the relationship between HSPB7 and ERK signaling pathway, Naderi found HSPB7 overexpression in breast cancer cells reduced the level of p-ERK [18].…”
Section: Discussionmentioning
confidence: 99%
“…APC was predicted as the potential target of miR-675 ( Figure 5A). APC is a negative regulator in the activation of Wnt/β-catenin pathway, which is closely related to the osteogenesis of MSCs [21,22]. Western blot results proved that APC was significantly decreased by miR-675 mimics and increased by miR-675 inhibitor.…”
Section: Mir-675 Targets Apc and Downregulates Apc Expression In Hamscsmentioning
confidence: 91%
“…As APC is a negative regulator in the Wnt/β-catenin pathway [ 27 ], APC overexpression was established in HBMSCs and the cells were assigned to the following groups: NC: HAMSCs + LPS + HBMSCs APC NC ; APC: HAMSCs + LPS + HBMSCs APC . Western blot analysis showed that APC overexpression increased the protein level of APC and decreased the protein level of β-catenin (Fig.…”
Section: Resultsmentioning
confidence: 99%